Inflammatorisk fordøyelsessykdom - fra partnerens synsvinkel - Øverlie, Anne; Grov, Ellen Karine; Ytrehus, Siri (Nordisk Tidsskrift for Helseforskning, 2018)
Inflammatory bowel disease leaves high physical, mental, social and existential burden on those facing the disease. Less is known about how their partners experience impact from the disease on their situation. From the perspective of the partners, this study describes the concerns highlighted by partners of persons with inflammatory bowel disease. The study has a qualitative design and in-depth interviews were performed to gather data. The sample consists of nine partners of persons with inflammatory bowel disease. Three main themes emerged: (i) uncertainty and helplessness, (ii) loss and (iii) attitudes and strategies to cope with concerns. A synthesis reveals the concept “caregiver-grief” comprising the relational and emotional concerns as well as how to deal with these concerns. Partners of persons living with inflammatory bowel disease describe grief and concern connected to their role as caregiver and spouse/cohabitant.